2020
DOI: 10.1002/ecs2.3216
|View full text |Cite
|
Sign up to set email alerts
|

Individual responses to novel predation risk and the emergence of a landscape of fear

Abstract: Elucidating changes in prey behavior in response to a novel predator is key to understanding how individuals acclimate to shifting predation regimes. Such responses are predicted to vary among individuals as a function of the level of risk to which individuals are exposed, temporal changes in risk, and landscape‐mediated changes in perceived risk. We tested how GPS‐tracked moose (Alces alces, n = 19) responded to an emerging risk landscape with the introduction of hunting to a naïve population (large‐scale red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
(98 reference statements)
1
2
0
Order By: Relevance
“…Accounting for moose density, relative hunting risk increased with moose density but decreased with increasing distance to bogs, distance to clearcuts and young forests, terrain ruggedness, building density, and distance to main and secondary roads. Some of these results are in accordance with previous studies and indicate that hunters predominantly kill moose in open terrains (e.g., bogs, clearcuts) (Ciuti et al, 2012;Lone et al, 2014) or in proximity to roads (Perry et al, 2020;Proffitt et al, 2013) and in areas characterized by low terrain ruggedness (Perry et al, 2020). The negative correlation between the occurrence of hunter-killed moose and building density is probably due to the highly skewed distribution of human settlements within our study area.…”
Section: Predictor Of Hunting Risksupporting
confidence: 92%
“…Accounting for moose density, relative hunting risk increased with moose density but decreased with increasing distance to bogs, distance to clearcuts and young forests, terrain ruggedness, building density, and distance to main and secondary roads. Some of these results are in accordance with previous studies and indicate that hunters predominantly kill moose in open terrains (e.g., bogs, clearcuts) (Ciuti et al, 2012;Lone et al, 2014) or in proximity to roads (Perry et al, 2020;Proffitt et al, 2013) and in areas characterized by low terrain ruggedness (Perry et al, 2020). The negative correlation between the occurrence of hunter-killed moose and building density is probably due to the highly skewed distribution of human settlements within our study area.…”
Section: Predictor Of Hunting Risksupporting
confidence: 92%
“…To investigate these potential population and community effects, it is necessary to compare the impacts of human and nonhuman predation risk on prey antipredator behaviors (Clinchy et al, 2016; Crawford et al, 2022; Suraci, Frank, et al, 2019). Examples of antipredator behavioral responses are changes in vigilance (Creel et al, 2014; Laundre et al, 2001; Schuttler et al, 2017), foraging (Smith et al, 2017; Van Beeck Calkoen et al, 2022), movement (Courbin et al, 2015; Crawford et al, 2022; Gehr et al, 2018), and resource selection (Perry et al, 2020; Stewart et al, 2022; Suraci, Clinchy, et al, 2019). Although studies have compared the impacts of human versus nonhuman fear on vigilance and foraging using auditory playbacks and cameras (Crawford et al, 2022; Smith et al, 2017), and used GPS data to investigate the impacts of hunters on movement and resource selection (Collier et al, 2017; Gross et al, 2015; Perry et al, 2020; Stewart et al, 2022; Sullivan et al, 2018), few studies have compared the impacts of human and nonhuman predation risk on movement and resource selection of prey.…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that visibility influenced the distribution of moose harvest locations, which is supported by moose harvest locations being disproportionally distributed in areas with higher proportions of clearcuts. The importance of visibility is more disputed in the literature (Perry et al, 2020 ) and ultimately depends on the hunting tactics (i.e., passive vs. active) used by hunters (Norum et al, 2015 ). Animals can perceive predators as a threat and in response allocate more time to antipredator behaviors (Lima & Bednekoff, 1999 ); however, spending more time hiding often comes at the expense of foraging opportunities and can carry substantial costs (Hertel, Zedrosser, et al, 2016 ; Lima & Dill, 1990 ).…”
Section: Discussionmentioning
confidence: 99%